The influence of a hot environment on parental cooperation of a ground-nesting shorebird, the Kentish plover Charadrius alexandrinus - AlRashidi, Monif (BioMed Central, 2010)
BACKGROUND: Parental care often increases offspring survival, but is costly to the parents. A trade-off between the cost and benefit of care is expected, so that when care provisioning by both parents is essential for the success of young, for instance in extremely cold or hot environments, the parents should rear their young together. We investigated the latter hypothesis in a ground nesting shorebird, the Kentish plover Charadrius alexandrinus in an extremely hot environment, the Arabian Desert. Midday ground temperature was often above 50°C in our study site in Abu Dhabi (United Arab Emirates), thus leaving the eggs unattended even for a few minute risks overheating and death of embryos. RESULTS: Through the use of video surveillance systems we recorded incubation routines of male and female Kentish plovers at 28 nests over a full day (24 h). We show that ambient temperature had a significant influence on incubation behaviour of both sexes, and the relationships are often non-linear. Coordinated incubation between parents was particularly strong in midday with incubation shared approximately equally between the male and the female. The enhanced biparental incubation was due to males increasing their nest attendance with ambient temperature. CONCLUSIONS: Our results suggest biparental care is essential during incubation in the Kentish plover in extremely hot environments. Shared incubation may also help the parents to cope with heat stress themselves: they can relieve each other frequently from incubation duties. We suggest that once the eggs have hatched the risks associated with hot temperature are reduced: the chicks become mobile, and they gradually develop thermoregulation. When biparental care of young is no longer essential one parent may desert the family. The relaxed demand of the offspring may contribute to the diverse breeding systems exhibited by many shorebirds.